Screening of nutritional status and education on balanced nutrition for boardingÂ schoolÂ students - Raden Edi Fitriyanto; Farida Juliantina Rahmawaty; Gloscindy Arma Occifa (Universitas Ahmad Dahlan, 2022)
Nutritional status is a condition that reflects the balance between nutrient intake and nutrient needs for body metabolism. Malnutrition is still a priority for national health development. Malnutrition in children causes growth and development problems and affects the quality of resources. The risk of malnutrition can occur to the students at the Islamic boarding school because they do not live and are cared for by their parents. Therefore, this community service focuses on screening and anticipating calorie deficiency in elementary school students. Ash Sholihah Islamic Boarding School is a boarding school in Sleman Regency with simple facilities. The number of boarding school students is approximately 700 male and female students, consisting of elementary to high school students. Elementary school students need more attention because they cannot take care of themselves and maintain food intake properly. The results of the anthropometric examination of 198 children showed that 166 (83.6%) were underweight, 24 (12.1%) had ideal body weight, and 8 (4.04%) were overweight. The results of the anthropometric examination of 198 children showed that 166 (83.6%) were underweight, 24 (12.1%) had ideal body weight, and 8 (4.04%) were overweight. The results of the mini nutritional assessment (MNA) questionnaire screening showed 10 (5.1%) malnutrition, 165 (83.3%) risk of malnutrition, 8 (4%) good nutrition, and 15 (7.6%) unknown. The service activities were continued with medical examinations and administration of drugs if necessary. Then carried out education and provision of additional calories to 166 children with underweight. Dormitory administrators are involved in supervising the implementation of additional nutrition. Additional intake given is a preparation equivalent to 100 kcal/day for each child as modified Formula 100.